Laser Induced Refractive Index Change in Nematic Liquid Crystals - Larraga, Crispulo; Palima, Darwin; Domingo, Zenaida (Science Diliman: A Journal of Pure and Applied Sciences; Vol 11 No 2 (1999), 2007)
We report the observation of laser induced refractive index change for a homeotropically aligned nematic liquid crystal (BDH-E7) film of 10 mm thickness. Diffraction rings were observed when an intense Ar+ ion laser hits a homeotropically aligned nematic liquid crystal at normal incidence above a threshold of 110 KW/cm2, which correspond to the threshold of the Optical Freedericksz Transition (OFT). Above the threshold, as the laser intensity was increased, the number of observed diffraction rings likewise increased. The mechanism for optical molecular reorientation has a great dependence on elastic restoring forces. By exploring the dependence of bend elastic constant, K33 with Freedericksz transition, the value of the K33 was calculated at 2.6 x 10-12 N. To investigate the behavior of Dn as a function of intensity, an experiment was performed for oblique laser incidence. It was shown that the refractive index change increased linearly from values of 0.00 1 to 0.18 at laser intensities ranging from 50 KW /cm2 to 200 KW /cm2. The Kerr coefficient n2 was calculated for various laser incidence angles.
Keywords: liquid crystals, refractive index, optical freedericksz transition, director reorientation, laser